Challenge of Relapse after Orthodontics Treatment and Bone Remodeling - Dr.drg. Tita Ratya Utari, Sp.Ort (Fakultas Kedokteran Gigi Universitas Hasanuddin, 2014)
Long term stability of an orthodontics treatment result is considered as one of success keys in orthodontics treatment. However, the occurance of a relapse (tooth movement into its original position) after the treatment remains a significat problem for orthodontist and becomes a challenge in orthodontics treatment.